P805 Fertility, conception and delivery in patients with IBD, a retrospective study in two centres in Greece. (25th January 2019) - Moschovis, D; Velegraki, M; Theodoropoulou, A; Zacharopoulou, E; Internos, I; Stylianou, K; Tzouvala, M
Abstract: Background: Patients with IBD are concern about fertility, conception and relapse of disease during pregnancy. Birth weight and pregnancy outcome seems to be related with surgical procedures and medical treatment. Methods: We evaluated these parameters in a retrospective analysis of Greek IBD patients. Results: In total 430 patients were registered, 212 men (49.3%) of median age 33 ± 14 and 218 women (50.7%) of median age 33.1 ± 14.5. The majority of them (54.9%) had Crohn's disease (CD). No children have been reported by 173 (41.2%) patients: 99 males (46.7%) and 74 females (33.9%), p = 0.005. The rest 257 patients (59.8%) had at least one child (average 1.92 kids per patient). Patients with children are statistically older than these without (39 ± 13.8 vs. 24.3 ± 9.7, p < 0.001). Caesarean section was performed in 34% of deliveries (168/494). Median age of the first conception was 27.6 ± 6 years old in both sexes. For the women, median age of first, second and third conception was 25.7 ± 5.4, 27.7 ± 5 and 28.4 ± 7 year olds, respectively. One third of patient had their first child after the IBD diagnosis ( n = 75, 29.2%), while 182 (70.8%) before.https://planner.smart-abstract.com/ecco2019/submission/en/abstract/13286/content#. Women with active disease at conception had clinical relapse during pregnancy more often than these with quiescent disease (37.5% vs. 4.8%, p = 0.005). Moreover, active disease in conception increased the risk of clinical relapse during pregnancy 12 times (ΟR = 12, 95% CI = 1.6–90). Relapse during pregnancy increased the risk of preterm delivery from 1.5% to 28.6% ( p < 0.001). Infant's weight was, as expected, statistically lower in preterm deliveries ( p < 0.001) as well as in pregnancies with relapse of IBD (2934 vs. 3227.5 g, p = 0.16). Infant's weight from parents with serious disease (surgery) was lower than these from parents without surgeries or parents that had children before IBD diagnosis (2754 ± 1089 vs. 3183.8 ± 521 vs. 3317 ± 571 g, respectively, p = 0.043). Additionally, infant's weight from parents that conceived after IBD diagnosis was lower compared with the infants that were before IBD diagnosis (3076 ± 490 vs. 3293.5 ± 567 g, p = 0.017). Conclusions: Fertility, conception, birth weight and outcome of pregnancies in Greek IBD patients do not differ from these published in other populations.